APLIKASI KOTAK SARAN MAHASISWA BERBASIS ANDROID PADA STMIK KRISTEN NEUMANN INDONESIA MEDAN - Lidia Megawati Br Kembaren; Mahdianta Pandia (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2019)
Good service quality in a university is one of the things expected by students. With the suggestionbox provided by STMIK Kristen Neumann Indonesia is one form to improve good service, butminimal students use the suggestion box because the criticisms and suggestions do not getimmediate response from the leadership, because the suggestion box is a one-way media. With theexisting problems and to take advantage of developments in information technology, the authorsbuild an Android-based student suggestion box application that can be directly responded by theleadership.